Mysticism and the renewal of Islamic literature - Altabaa, Homam; Hamawiya, Adham (IIUM Press, International Islamic University Malaysia, 2019)
Literature has been a medium to express and explore the depths of human life and Truth. This is accurate of Islamic literature, produced across the globe over hundreds of years. This paper seeks to highlight key mystical aspects of classical Islamic literature and their relevance to world literature and culture. Mysticism is essentially understood in this context as a set of beliefs and practices that lead to a form of proximity or union with the Divine. The paper explores its key manifestations in prominent works of Islamic literature by renowned classical figures such as Rumi, Ibn ‘Arabī, ’Al-Ghazālī, Ibn ‘Al-Fāriḍ and Rābi‘ah. These manifestations include prevalent themes such as divine essence and attributes, gnosis and knowledge, the concept of mystical path and divine love. The paper concludes that contemporary Muslim writers and literary commentators are left with a rich tradition that can be re-examined, revived and matched to renew and rejuvenate the literatures of Muslim nations.